Standards of living and human potential development: Assessing risks to regions’ economic security - Gleb A. Maslov; Yulia A. Sherstobitova (Journal of New Economy)
The possibility of high-quality labour force reproduction is a key condition for forming a knowledge-intensive production system, ensuring the necessary level of technological sovereignty and economic self-sufficiency against the background of the deteriorating geo-economic situation. The study’s aim is to identify and assess the risks to economic security in the context of human potential development on the example of regions in Russia’s Volga Federal District. Methodologically, the re search relies on Senchagov–Mityakov zonal theory as well as on a political economy approach. The methods include a historical-logical method, comparative analysis, and an index method. The data is the indicators reflecting the standard of living and the degree of human potential development for 2010–2022 coming from the Federal State Statistics Service of the Russian Federation. The decile ratio and the percentage of population with income below the subsistence level capture the greatest risks to regional economic security. The problem traced by the decile ratios is the acutest in the Perm krai and the Nizhny Novgorod oblast, in terms of poverty – in the Mari El Republic, the Chuvash Republic, and the Republic of Mordovia. The most favourable situation has emerged with the unemployment rate, especially in such industrially de veloped regions as the Republic of Tatarstan, the Udmurt Republic, and the Republic of Bashkortostan. The findings confirm the need for an active state policy focusing on the development of social sphere and reduction of inequality, prioritising the development of the institutional environment, and expanding financial incentives in the innovative segment of the national economy.